Brown Adipose Stem Cell-Loaded Resilin Elastic Hydrogel Rebuilds Cardiac Function after Myocardial Infarction via Collagen I/III Reorganisation - Le Zhao; Huaying Liu; Rui Gao; Kaihui Zhang; Yuxuan Gong; Yaya Cui; Shen Ke; Jing Wang; Haibin Wang (Gels, 2024)
Irreversible fibrosis following myocardial infarction (MI) stiffens the infarcted myocardium, which remains challenging to restore. This study aimed to investigate whether the injectable RLP12 hydrogel, derived from recombinant resilin protein, could serve as a vehicle for stem cells to enhance the function of the infarcted myocardium. The RLP12 hydrogel was prepared and injected into the myocardium of rats with MI, and brown adipose-derived mesenchymal stem cells (BADSCs) were loaded. The survival and differentiation of BADSCs in vivo were investigated using immunofluorescence one week and four weeks after treatment, respectively. The heart function, MI area, collagen deposition, and microvessel density were further assessed four weeks after treatment through echocardiography, histology, immunohistochemistry, and immunofluorescence. The RLP12 hydrogel was prepared with a shear modulus of 10–15 kPa. Four weeks after transplantation, the RLP12 hydrogel significantly improved cardiac function by increasing microvessel density and reducing infarct area size and collagen deposition in MI rats. Furthermore, the distribution ratio of collagen III to I increased in both the centre and edge areas of the MI, indicating the improved compliance of the infarct heart. Moreover, the RLP12 hydrogel also promoted the survival and differentiation of BADSCs into cardiac troponin T- and α-smooth muscle-positive cells. The RLP12 hydrogel can be utilised as an injectable vehicle of BADSCs for treating MI and regulating collagen I and III expression profiles to improve the mechanical microenvironment of the infarct site, thereby restoring heart function. The study provides novel insights into the mechanical interactions between the hydrogel and the infarct microenvironment.